SISTEM PENGONTROLAN KELEMBABAN TANAH DENGAN KONTROL LOGIKA FUZZY BERBASIS ARDUINO UNO PADA PERANGKAT SMART GREENHOUSE UNTUK TANAMAN HIAS PURING - Affan Affandi; Muhammad Aziz Muslim; Goegoes Dwi Nusantoro (Jurnal Mahasiswa TEUB, 2022)
During the Covid-19 pandemic, caring for ornamental plants was one of the activities that many people liked, resulting in a drastic increase in demand for ornamental plants. However, the process of caring for plants that can bring out their uniqueness is very difficult. The puring plant (Codiaeum Variegatum) is an ornamental plant that is unique in its leaves, the puring plant grows in tropical climates, and requires sufficient water. The benefit of croton plants is that they can degrade the pollutants around them. To optimize the care of croton plants, a device is needed that can meet the water needs of croton plants. The research begins with designing device designs and control systems. Followed by assembling the prototype device and testing it according to the characteristics of the croton plant. Furthermore, data collection and analysis were carried out using the Mamdani method of fuzzy logic control. The fuzzy logic control will regulate the soil moisture needed by croton plants, with a setpoint of 30%RH which is the ideal humidity for croton plants. The test results show that the device can function according to the design that has been made.Keywords: Croton Plant, Fuzzy Logic Control, Mamdani Method, Soil moisture